Low carbon urban development strategy in Malaysia - the case of Iskandar Malaysia development corridor - Chin, Siong Ho (elsevier, 2013)
Sustainability policies that have quantitative emission or carbon footprint measurements are important in view of climate change and current rapid urbanization in developing countries like Malaysia. Although sustainability policies are mentioned in national development plan as early as in the 1990s, many of these policies are piecemeal and expressed qualitatively. In achieving environmental sustainability, planning of city or a region can be more functional and implementable by using low carbon city concept. Planning a low carbon city uses sustainable development principles; this demonstrates a high level of energy efficiency using low carbon energy sources and production technologies. It also adopts patterns of consumption and behavior that are consistent with low levels of greenhouse gas emissions in the urban areas. The planning of the fast developing region of Iskandar Malaysia, which is located in southern part of Peninsular Malaysia, provides a good opportunity for urban managers to incorporate the ideas of low carbon cities in this proposed high growth urban conurbation. This paper aims to explore implementation of the concept and vision of low carbon scenarios and examine the strategies toward the reduction of CO 2 emission. This study also prepares a quantitative scenario study on the establishment of low carbon urban development in Iskandar Malaysia.